2010
DOI: 10.1002/ptr.2872
|View full text |Cite
|
Sign up to set email alerts
|

Glabridin inhibits lipopolysaccharide‐induced activation of a microglial cell line, BV‐2, by blocking NF‐κB and AP‐1

Abstract: Glabridin, a flavonoid present in licorice root, is known to have antiinflammatory and cardiovascular protective activities. The present study reports an inhibitory effect of glabridin on microglial activation. Glabridin dose-dependently attenuated lipopolysaccharide (LPS)-induced production of inflammatory mediators, including nitric oxide, tumor necrosis factor-alpha and interleukin-1beta, in BV-2 cells, a murine microglia cell line. Moreover, mRNA expression of these inflammatory mediators was also suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
5
23
0
Order By: Relevance
“…4). In accordance with our data, most compounds which produce anti-inflammatory effects inhibit AP-1 and NF-κB activation Lee et al, 2005;Bae et al, 2006;Jang et al, 2008;Yang et al, 2009;Park et al, 2010). Our present results indicate that visnagin can also inhibit activation of AP-1 and NF-κB in LPS-stimulated microglial cells.…”
Section: Discussionsupporting
confidence: 95%
“…4). In accordance with our data, most compounds which produce anti-inflammatory effects inhibit AP-1 and NF-κB activation Lee et al, 2005;Bae et al, 2006;Jang et al, 2008;Yang et al, 2009;Park et al, 2010). Our present results indicate that visnagin can also inhibit activation of AP-1 and NF-κB in LPS-stimulated microglial cells.…”
Section: Discussionsupporting
confidence: 95%
“…Consistent with previous reports on the signal pathways underlying microglial activation, we observed that MAPKs such as ERK-1/2, JNK and p38 signaling pathways were involved in LPSstimulated BV-2 microglial activation (Ock and Suk, 2010;Park et al, 2010). MAPK's have been shown to be important upstream modulators for inflammatory cytokine and NO production in a variety of biological systems (Jongeneel, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we showed that glabridin inhibited the activation of NF-κB by blocking the degradation of IκBα/β and the nuclear translocation of p65/p50 in LPS-treated DCs. Consistent with this study, glabridin inhibited NF-κB activation in RAW 264.7 macrophages and BV2 microglial cells [5,26,30]. MAPK signaling pathways also play a major role in DC maturation [29,31,32].…”
Section: Discussionsupporting
confidence: 73%
“…BV2 microglial cells, specialized macrophages in the brain, were also reported to be target cells of glabridin. Glabridin inhibited LPSinduced production of inflammatory mediators including NO, TNF-α, and IL-1β in BV2 cells [26].…”
Section: Discussionmentioning
confidence: 99%